1999
DOI: 10.1002/(sici)1097-4628(19990523)72:8<1031::aid-app7>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Studies on sand/clay unsaturated polyester composite materials

Abstract: The effect of a radiation-initiated polyester on the physicomechanical properties of a sand/clay-polyester composite has been investigated. The unsaturated polyester resins containing various styrene contents were used at different sand/clay composites from 10 to 70 wt % with respect to the weight of sand and clay together; polymerization was conducted using ␥-irradiation at 50 kGy. Also, different particle sizes of clay (namely 1.25-0.80, 0.80 -0.50, and Ͻ0.50) were used. The compressive strength, apparent po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 8 publications
1
20
0
Order By: Relevance
“…Some investigations also showed the similar tendencies for the clay/polypropylene, nylon, or polyester composites 13, 16, 17. The previous study21 pointed out that the physical properties (especially the tensile strength) of the nanometer particle/resin composite were higher than that of resin alone. Here, we are interested in the differences between the composite films that were produced under roller pressure and under nonroller pressure.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Some investigations also showed the similar tendencies for the clay/polypropylene, nylon, or polyester composites 13, 16, 17. The previous study21 pointed out that the physical properties (especially the tensile strength) of the nanometer particle/resin composite were higher than that of resin alone. Here, we are interested in the differences between the composite films that were produced under roller pressure and under nonroller pressure.…”
Section: Resultsmentioning
confidence: 70%
“…Chen et al20 used organophilic clay to be added to poly(3‐hydroxybutyrate‐ co ‐3‐hydroxyvalerate) chloroform solution to study the effect of nanometer clay particle on the crystalline kinetic of PHVB/clay composite and found that the organophilic clay nanometer particle could affect the crystallization temperature of the composite. Sand/clay–polyester composite was invesgated21 and found that the unsaturated polyester would react with clay under γ‐irradiation to form a stable composite and improve the strength of polyester. Here, it was interesting to find that the nanometer particle of zirconium carbon could be sufficiently wetted and dispersed in polyurethane‐ (PU) solvent solution under the suitable roller pressure to form a good strength of the films and these were formed from this composite.…”
Section: Introductionmentioning
confidence: 99%
“…Clay minerals such as bentonite, kaolin, talc, and mica are often used as inorganic fillers in conventional polymer composites to reduce their cost and/or to impart special properties such as high modulus, hardness, thermal stability, electrical insulation, thickening, opacity, and brightness [12][13][14][15][16]. Heat insulation materials available on the local market are relatively expensive and are mostly used by local contractors and small-size entrepreneurs.…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in thermal conductivity with an increase in porcelain content is in agreement with results reported by Budnikov (1964). It is assumed that with the increase of porosity the mean free path decreased resulting in lower thermal conductivity (Kingery, 1962;Ismail et al, 1999). It is also assumed that lower thermal conductivities of PPCs may also be due to the insulating properties of porcelain and heterogeneity of structure.…”
Section: Determination Of Thermal Conductivities Of Ppcsmentioning
confidence: 99%